2015
DOI: 10.1039/c5fo00507h
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-diabetic activity of peony seed oil, a new resource food in STZ-induced diabetic mice

Abstract: This study was conducted to investigate the components of a new resource food in China, peony seed oil (PSO) by GC-MS (gas chromatography-mass spectrometry), its inhibitory effects on carbohydrate hydrolyzing enzymes in vitro and its anti-diabetic effects on mice induced by streptozotocin (STZ). The results showed that peony seed oil showed weak anti-α-amylase activity; however, strong anti-α-glucosidase activity was noted. The GC-MS analysis of the oil showed 9 constituents of which α-linolenic acid was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…In 2011, at China, peony seed oil (PSO) was declared as a new resource food for high level of α‐linolenic acid (≥38%, Ministry of Health 2011 Number 9 China), Li compared fatty acids in 60 tree peony cultivars, the result indicated that the ratio of n‐6/n‐3 was between 0.4 and 1.6 and the ratio of n‐3/ total fatty acids was greater than 38% (Li and others ). The antidiabetic activity of PSO has been verified in our previous report (Su and others ), however no reports are available on the hypolipidemic effects of PSO used as dietary supplement in rats fed with high fat diet.…”
Section: Introductionmentioning
confidence: 65%
“…In 2011, at China, peony seed oil (PSO) was declared as a new resource food for high level of α‐linolenic acid (≥38%, Ministry of Health 2011 Number 9 China), Li compared fatty acids in 60 tree peony cultivars, the result indicated that the ratio of n‐6/n‐3 was between 0.4 and 1.6 and the ratio of n‐3/ total fatty acids was greater than 38% (Li and others ). The antidiabetic activity of PSO has been verified in our previous report (Su and others ), however no reports are available on the hypolipidemic effects of PSO used as dietary supplement in rats fed with high fat diet.…”
Section: Introductionmentioning
confidence: 65%
“…Enzymatic antioxidants, such as SOD and GSH-Px, have been considered as primary enzymes since they were involved in the direct elimination of reactive oxygen species (ROS) [ 44 ]. MDA is thought to be an indicator of the lipid peroxidation process [ 45 ]. Four-week PHC administration has successfully normalized the disordered levels of SOD, GSH-Px, and MDA in kidney of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Linoleic acid, oleic acid and linolenic acid are responsible for antioxidant function, reduces blood fat and cholesterol and prevents head blood vessel diseases. Linolenic acid also has the effect of anti-inflammatory, improving intelligence and vision (Bourourou et al, 2016), but it cannot be synthesised in the human body (Sevim et al, 2013;Su et al, 2015).…”
Section: Introductionmentioning
confidence: 99%